Efficacy of indirect ELISA for serodiagnosis of melioidosis using immunodominant antigens from non-pathogenic Burkholderia thailandensis - Wajanarogana, Sumet (Springerplus, 2016)
Melioidosis caused by gram negative bacteria, B. pseudomallei, is a fatal disease in the tropical and sub-tropical regions. However, sporadic cases have been reported in elsewhere. Early detection is imperative to reduce the mortality rate. Serological tests have being substantially developed using recombinant proteins as specific targeted antigens to melioidosis antibodies. In the present study, we focus on a truncated flagellin fragment (FLAG300) and outer membrane protein A (OmpABT) of B. thailandensis E264 as potential antigens for developing indirect ELISA to improve the serodiagnosis of melioidosis. Recombinant proteins were overexpressed and purified by immobilized metal affinity chromatography with denaturing conditions. The sensitivity and specificity of individual test were calculated within culture-confirmed melioidosis sera (n = 42) and non-melioidosis serum samples (n = 241) using the cut-off point at average of absorbance plus 2 standard deviations. The results demonstrated that a FLAG 300 based indirect ELISA showed 90.48 % sensitivity and 87.14 % specificity and an OmpABT based this assay revealed sensitivity of 80.95 % and specificity of 89.21 %. Their use in a double-antigen ELISA resulted in improve specificity (92.95 %) and still high degree of sensitivity (85.71 %). These data suggest a facile method for serodiagnosis of melioidosis by the use of antigens from a non-pathogenic strain.